Accelerated hip fracture surgery in the elderly: A pilot study / Komella Anne Sooria Prakasam - Komella Anne, Sooria Prakasam (2018)
BACKGROUND: The rising incidence of hip fractures in the elderly is a healthcare burden in terms of morbidity, mortality and costs that can be reduced by accelerating surgery. Hip fractures initiate an inflammatory response, resulting in a catabolic, procoagulant, stressed state that may result in further complications in an already vulnerable, immobile group of patients. Hastening surgery shortens the duration of the body’s exposure to these harmful states and may reduce complications and improve patient outcome. OBJECTIVES: The primary objective of this pilot study is to compare mortality rates and major peri-operative complications in patients who underwent accelerated surgery versus standard waiting times. The secondary objectives looked at length of hospital stay and time taken to mobilise after surgery. METHODS: Patients who fulfilled the inclusion criteria such as age more than 45 years and diagnosed with a hip fracture were recruited. Patients were then randomly assigned to either an accelerated group who had surgery done within 6 hours of diagnosis or a standard group who followed standard operating times. These patients were then followed up to compare morbidity, mortality, time taken to mobilise after surgery, length of hospital stay and Functional Independence Measure mobility scores at 30- days. RESULTS: There was statistical significance between the preoperative waiting time of the 2 groups (5.44 hours vs 51.05 hours, p<0.001). For the other measured variables, there were no statistically significant differences noted the 2 groups; time to mobilisation (25.17 hours vs 29.05, p=0.450), length of stay in hospital (6.11 days vs 6.58 days, p=0.824) and length of postoperative stay in hospital (5.89 days vs 4.37 days, v p=0.482) and 30 day FIM scores between the 2 groups (51.4 vs 58.88, p=0.390). Both groups had 2 cases of death among its subjects. In addition to the deaths, 1 subject in the accelerated group was complicated with a surgical site infection while 1 subject had a periprosthetic hip fracture in the standard group. However, there was no significant differences in the 30-day perioperative complications rate between the 2 groups (16.7% vs 14.3%, p=1.000). CONCLUSION:This pilot study revealed the feasibility to conduct accelerated surgery on a larger scale to study the effect on 30-day perioperative complications, time to mobilisation, length of postoperative stay and 30-day FIM scores.